Prevalence of Intestinal Parasitic Infections and Genotypic Distribution with Risk Factors of Enterocytozoon bieneusi in HIV Patients of Maesai Hospital, Thailand - Khositharattanakool, Pathamet; Somwang, Puckavadee (Trends in Sciences, 2022)
Co-infections of HIV and intestinal parasites including Enterocytozoon bieneusi (E. bieneusi) are a common cause of gastrointestinal syndrome in HIV-infected people. Our study was designed to detect infection rates of intestinal parasites and the genotypic distribution of E. bieneusi, as well as probable risk factors for infection in HIV patients at Maesai hospital, Chiang Rai, Thailand. Two hundred and twenty-four stool samples from enrolled HIV-infected participants were collected and examined for parasitic infections, using microscopy and polymerase chain reaction techniques. CD4 status as well as the demographic data of HIV-infected participants was also collected and analyzed. Intestinal parasites including E. bieneusi were detected in 4.02 % of all participants. The highest intestinal parasitic infection rate was E. bieneusi (2.23 %) followed by Strongyloides stercoralis (1.34 %), Opisthorchis viverrini (0.89 %) and Giardia intestinalis (0.45 %). Intestinal parasitic infection rate of participants with CD4 count ≤ 200 cells/mm3 was significantly higher than that of participants with CD4 counts > 200 cells/mm3 (12.50 % vs 2.63 %, p = 0.027). Correspondingly, the infection rate of E. bieneusi was significantly higher in participants with CD4 count ≤ 200 cells/mm3 than in participants with CD4 count > 200 cells/mm3 (9.38 % vs 1.05 %, p = 0.022). Two genotypes of E. bieneusi, including D (n = 3) and SH8 (n = 2), were identified from 5 participants. Both of the identified genotypes were likely a zoonotic transmission. Human infection by E. bieneusi genotype SH8 was a discovery for the first time in Thailand. However, no intestinal coccidian infections were diagnosed. The low numbers of intestinal parasitic infections of this study were probably due to wide availability of antiretroviral therapy, improved health sanitation, as well as ease of access to antiparasitic medication in HIV-infected people. HIGHLIGHTS We discovered that HIV patients at Maesai Hospital had a low prevalence of both opportunistic and non-opportunistic intestinal parasitic infections, which was probably due to health improvement and treatment availability We discovered Enterocytozoon bieneusi genotypes D and SH8 in HIV patients. Human infected with genotype SH8 was the first to be reported in Thailand Low levels of CD4 cells and contact with animals were considered to be risk factors for infection with bieneusi genotypes D and SH8 GRAPHICAL ABSTRACT